Bitterballen Formulation of Chicken Meat, Sorghum Flour, and Green Spinach as an Alternative Additional Feeding For Stunted Toddlers Age 12-23 Months - Nindya Az Zahra; Theresia Puspita; I Nengah Tanu Komalyna (International Journal of Medical Science and Clinical Research Studies, 2024)
Lack of nutrition in children and stunting may be caused by several interrelated factors. One of the factors that can influence the emergence of growth retardation in children under five is a lack of food intake such as protein, energy, and zinc children failing to grow. This research analyzes the nutritional values, organoleptic quality, and best level of treatment for Bitterballen with a formulation of chicken meat, sorghum flour, and green spinach as an alternative for providing additional food to stunted toddlers aged 12-23 months. The approach used is quantitative and qualitative by analyzing the organoleptic quality results of Bitterballen, determining the best formulation treatment, and calculating the nutritional value using the yield factor and retention factor for each treatment. The manufacturing procedure was first carried out by formulating three treatments with a ratio of chicken meat, sorghum flour, and green spinach. Of all the treatments, treatment 1 had the highest acceptability, namely containing 287.86 kcal of energy with a nutritional value of 12.71 grams of protein, 17.93 grams of fat, and 19.48 grams of carbohydrates. The organoleptic quality produced by T1 is that it has a light brown color, the aroma is savory, not fishy, and not rancid, the taste produced by T1 is savory and not unpleasant, with the inner texture produced by T1 is not gritty and the outer part is crunchy. The aftertaste is savory and slightly gritty.